O espaço agrário de gado bravo PB : a produção agropecuária nas unidades camponesas - Leal, João Antério de Aguiar (2024)
Agriculture is the sector of the economy that encompasses the set of productive units that carry out their activities directly linked to nature. The activity stands out in various perspectives over the centuries: Economic, although currently the agricultural sector represents a small portion of the national Gross Domestic Product (GDP); Historical, as it has been important in the process of formation of various localities and regions, as well as contributing to the territorial expansion process of Brazil; Social, taking into account the generation of employment in rural areas, as well as favoring the permanence of people in the countryside. Furthermore, agricultural activity is largely responsible for feeding the Brazilian population, especially when it comes to family farming. Therefore, the central objective of this research is to understand the productive organization of agriculture in peasant properties in the municipality of Gado Bravo, considering the location in question as an interesting point of analysis to understand the global context of agricultural activity from the perspective of peasant production from a micro level. Thus, we structured the work into three main parts: first, we present a theoretical framework that we consider important in order to understand the overall context of the object of study. Then, we propose to analyze the agricultural space in Gado Bravo in a more generalized way, addressing issues that go beyond agricultural activity. Finally, in the third part, we focus on aspects that permeate local agricultural production. To this end, we used bibliographic review, statistical data collection, and field study in Gado Bravo, including conducting interviews. After the analysis, we can conclude that the municipality of Gado Bravo constitutes a particular case in the state's reality due to the importance that its agricultural space still holds in the socio-economic dynamics, characterized by the low level of concentration of land ownership, the ability to retain its population in rural areas, and the weight of peasant production in the municipal primary sector.